Pengaruh Pembelajaran Role Playing Terhadap Peningkatan Critical Thinking Siswa Kelas XI Ekonomi di SMAN 8 Padang - Desi Rahmadani; Yulhendri Yulhendri (Universitas Negeri Padang, 2022)
This study aims to determine the effect of the role playing model on improving students critical thinking skills and to determine the process of implementing the role playing model on improving students critical thinking skills. This study uses a quasi-experimental design using a nonequivalent control group design model. Before being given treatment, the class that uses role playing is given a test, namely a pretest, with the intention of knowing the condition of the group before treatment, namely class XI MIPA 4 and after the treatment the group is given a posttest to see the improvement of the group by using the role playing learning model. The data analysis method used is hypothesis analysis. The results of this study indicate that the achievement of students' critical thinking results using the role playing model before being given treatment is lower than after being given treatment. So it is suggested that further researchers can examine game-based learning models on economic material, besides that it is hoped that other cooperative learning models can improve students' critical thinking outcomes and results their research later increase their contribution in improving the quality learning